Transfer Pricing and the Arm's Length Principle under Imperfect Competition - Jay Pil Choi; Taiji Furusawa; Jota Ishikawa (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyzes incentives of a multinational enterprise to manipulate an internal transfer price to take advantage of corporate-tax differences across countries under both monopoly and oligopoly. We examine “cost plus” and “comparable uncontrollable price” as two alternative implementations of the so-called arm's length principle (ALP) to mitigate this problem. Tax-induced foreign direct investment (FDI) may entail inefficient internal production. We show how the mechanisms behind such inefficient FDI differ between alternative implementation schemes of the ALP and explore implications of the ALP for welfare and dual sourcing incentives. We also develop a novel theory of vertical foreclosure as an equilibrium outcome of strategic transfer pricing.
Keywords: F12; F23; H26; L12; L13; L51; L52; 330; foreign direct investment; multinational enterprise; corporate tax; transfer pricing; arm's length principle; vertical foreclosure